Analysis of Literacy and Halal Awareness for Stakeholders Around the University of Trunojoyo Madura - Muhammad Ersya Faraby; Dahruji; Taufiqur Rahman; Ahmad Makhtum (Universitas Islam Negeri Alauddin Makassar, 2024)
Statistical data records that the Muslim population in Indonesia in 2023 will be 240.62 million people or the equivalent of 86.7 percent of the total population, 277.53 million people. This research aims to analyze stakeholders' literacy understanding and halal awareness around Trunojoyo Madura University. Halal literacy is a person's understanding of implementing halal principles in business activities, while halal awareness is a form of awareness of consumption activities regarding halal food, drinks and products. The approach used in this research is qualitative with a descriptive case study method. Data collection was carried out by a literature study. The analysis found that stakeholders still have low literacy and halal awareness, especially business actors and consumers. The role of the halal center and the halal inspection agency at Trunojoyo Madura University and the local government through the halal task force is expected to be able to increase halal literacy and awareness among stakeholders, especially around the Trunojoyo Madura University campus.